Pollen morphology of Ukrainian species of the genus Pedicularis L. (Orobanchaceae Vent.) - Peregrym, Olena M.; Tsymbalyuk, Zoya M.; Mosyakin, Sergei L. (Biodiversity: Research and Conservation, 2012)
Pollen grains of 10 species of Pedicularis occurring in Ukraine were investigated using light and scanning electron microscopy. Palynological data on 6 species are reported for the first time. General pollen morphology of the genus Pedicularis is presented. Three types of apertures (2-syncolpate, 3-colpate, and 3-syncolpate) and seven subtypes of sculpture (3-syncolpate pilate, 3-syncolpate microscabrate-tubeculate, 2-syncolpate microscabrate, 2-syncolpate microscabrate-tubeculate, 2-syncolpate microscabrate-tubeculate-perforate, 2-syncolpate microfoveolate, and 2-syncolpate microscabrate-perforate) are indentified. The subgenus Pedicularis is heterogeneous in its types of apertures and sculpture of the surface, which indicates the need of further taxonomic revision of the group.